Vórtice ciclônico em altos níveis e corrente de jato do nordeste brasileiro em anos de El Niño e La Niña. - Repinaldo, Henrique Fuchs Bueno (2010)
The connection between Upper Tropospheric Cyclonic Vortex (UTCV) and Brazilian Northeast Jet Stream (BNEJS) was analyzed for 9 years between 1988 and 2000, separated by El Niño, La Niña and Neutral years. Through the reanalysis products from NCEP, and METEOSAT satellite images in the infrared channel, were observed 167 UTCVs, most of them originated over the Atlantic Ocean with an average last of 4 days and showed no significant variability in years of El Niño and La Niña. Approximately 54% of the observed UTCVs were associated to air currents superior than 20m.s-1 in its periphery, these currents are called BNEJS. In El Niño years was observed an increase of BNEJS cases associated to UTCV, while in La Niña years, the number of occurrences was practically the same as in neutral years. The BNEJS showed intensitity up to 40 m.s-1, and the most observed wind directions were from south, southeast, northwest and west. Thus, 3 patterns of occurrence of BNEJS were identified, named Meridional, Zonal and Transversal. The Meridional BNEJS occurs in the UTCVs west periphery, usually over the continent, showing the upward movements between the BNEJS and the Northern Subtropical Jet Stream (NSJS). And finally, the transversal BNEJS, showed two kinds of currents, one from southeast and another from northwest. In these cases, the UTCVs axis showed an inclination to west and the upward movements were observed in the UTCVs periphery, where the winds were weaker. Thus, three cases were chosen to represent the observed patterns and investigate the vertical movements, comparing to the cloudiness in the satellite images, where was observed, in both cases, that the upward movements doesn t exists or are too weak in the jet streak BNEJS area.